Paleomagnetism of Permian-Triassic volcanic sequences from Son La province, northwest Vietnam - Chi, Cung Thuong; Geissman, John W.; Borgfeldt, Taylor; Hoang, Nguyen (Vietnam Journal of Earth Sciences, 2021)
Nineteen sites with 198 oriented-core samples have been collected from the Upper Permian-Lower Triassic volcanic rocks of Vien Nam Formation at Quynh Nhai locality, Son La Province, northwestern Vietnam. The characteristic remanent magnetization components carried by magnetite and hematite were successfully isolated from secondary components reveal a mean paleomagnetic direction Ds = 48.3°, Is = -10.0°, a95 = 8.0°, corresponding to a virtual geomagnetic pole located at l = 35.7°N, f = 217.4°E and a paleo-latitude of study area situated at 5.1°S during the Permian time. Compared with the Late Permian-Early Triassic pole of the South China Block (SCB), the data show that crustal elements of NW Vietnam have been close to, but not unequivocally a coherent part of the SCB, since the Late Permian. Development of the parallel NW-SE striking Song Ma and Song Chay orogenic belts did not involve the closure of wide (> 500 km) ocean basins.